UTILIZATION OF PRINT MEDIA AND VISUAL MEDIA ON ADOLESCENT KNOWLEDGE ABOUT ANEMIA - Ratna Hamidah; Ratih Kurniasari (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background: Anemia decreases hemoglobin levels, hematocrit, and red blood cell counts below the average values set for individuals. Anemia is more common in young women because young women experience menstruation, and blood loss during menstruation can cause anemia. Adolescent boys and girls in their growth period need more energy, protein, and other nutrients than other age groups. Anemia in adolescents will impact decreased concentration in learning, decreased physical fitness, and impaired growth so that height and weight are not average. The common knowledge of adolescents about health information, especially about anemia, requires efforts to overcome the problem of anemia. This study aims to present an overview of the use of print media and audio-visual media for knowledge of adolescents about anemia. Research Methods: The method used by the author in this study is to use some of the existing literature related to the title of this study. Research Result: The results and discussion of this study will help readers and health workers understand the planning steps in education using print media and audio-visual media to adolescents about anemia. Conclusion: Using audio-visual media in animation and media in the form of guidebooks and flashcards is considered adequate for increasing knowledge of anemic adolescents, and flashcard media are still rarely used for learning media.